Pengembangan Desa Cinta Statistik Sebagai Upaya Percepatan Penguatan Statistik Sektoral di Desa Selatbaru - SITI SUHAILA; Anne Mudya Yolanda; Rustam Efendi; Sukamto; Musraini M; Syamsudhuha; Gustriza Erda; Yenita Roza; Gumanti; M. SYIFA RAMADHAN; Althoff Hibban; Dimas Abyan Fatkhin Al-Aswad; Fandi Gusriyanda; Sarasmita Apriyenti; Adia Syaputri; Nusantri Purba; Nurhaliza; Okta Bella Syuhada (Journal of Community Engagement Research for Sustainability, 2024)
The Desa Cinta Statistik (Cantik) program aims to improve the quality of statistical data produced by increasing literacy, awareness and the active role of village officials and the village statistical community. This program is also a form of the Statistics Study Program's participation in the implementation of community service and is a collaboration between the Statistics Study Program (lecturers and students of Real Work Lectures) with BPS and Villages. The activities carried out in the form of assisting village officials in improving sectoral data and village-specific data are expected to suffice the availability of data for village development as one of the efforts to make One Data Indonesia successful. This program will be implemented in Selat Baru Village, Bengkalis Regency. Based on the data that has been collected, there are several work programs carried out by the Selatbaru Integrated Community Service Program (Cinta Statistik) Selatbaru Team in 2022. Village officials as non-productive partners have improved their sectoral data management capabilities. The outputs of the activity are the publication of Selatbaru Village statistics, Selatbaru Village Profiles and Statistics, Infographics, Monographs, and Videographics.